THE EFFECTIVENESS OF EM4 USE ON GROWTH OF CAYENNE PEPPER (Capsicum frutescens L.) - Shalahuddin Mukti Prabowo; Sangrani Annisa Dewi; Dwi Susilarto (Agric, 2018)
Cayenne pepper is one type of vegetables that have high economic value. Cayenne pepper as one of the many vegetable commodities cultivated by farmers in Indonesia because it has a high selling price. This study aims to analyze the effect of microbes by using EM4 on chili plants and assess the dose and time of EM4 application that is effective against the growth of cayenne pepper plant. The research method used was experiment, that is factorial experiment by using Randomized Complete Random Design (RAL) design with two treatment factors, EM4 dose (D) : D1= 5 ml/L, D2 = 10 5 ml/L, D3 = 20 ml/L and EM4 (T) time: T1= 5 HT, T2 = 10 HST, T3= 15 HST and. In total there are 10 treatment combinations with one control treatment (D0T0), with each treatment 3 plants and 3 replications, so there are 90 plants. The results showed that EM4 dosage with 15 days application time was the best combination of treatment for plant height, plant biomass and root length.